Determinantes dos óbitos infantis hospitalares e não hospitalares nos municípios do Vale do Jequitinhonha, Minas Gerais - Tatiane Rezende Petronilho Henriques (2019)
Introduction: Infant mortality (MI) is an indicator of health inequities and has a multifactorial etiology. The determinants related to child deaths point to circumstances of socioeconomic fragility, disparities in access and health care. The place of death, which may occur in or outside hospitals, is one of the situations that signals the characteristics of fragility. Thus, understanding the chain of events that can trigger deaths in population subgroups is critical. Objective: To Analyze the determinants of infant and non hospital deaths in the municipalities of Vale do Jequitinhonha, Minas Gerais. Methodology: This is a crossectional, retrospective study with secondary data analysis. Data from the mortality and birth banks of the Ministry of Health, between 2009 and 2014 years, were used. Demographic, socioeconomic and biological variables of pre-natal, childbirth and birth were analyzed. For The analysis of the association between the occurrence of infant and non hospital deaths with the study variables, logistic regression was performed with the odds ratio as a measure of association. A trend analysis of infant mortality was Also performed through the mixed logistic regression model with random effects. Results: In The study period 54,319 live births ofwhich 849 died in the first year of life were analyzed. The results showed a predominance of deaths in theearly neonatal period in hospitals and the proportion of infant deaths outside the hospitals was higher inthe post-neonatal period. In the final model, children who were born prematurely, with low birth weight and apgar less than seven in the fifth minute of life presented significant association with hospital and non hospital infant death. Children whose mothers had less than seven years of schooling and lived in regions of greater social vulnerability had a greater chance of dying outside the hospitals. Moreover, children of mothers who did not have a partner, who made up to six prenatal consultations, male children, with some type of anomaly, apgar less than seven in the first minute of life, were significant determinants only for the occurrence of infant death in hospitals. In the trendanalysis, it was observed that the deaths tended to decrease, but the decrease in the study period was not significant. Conclusion: The determinants of deaths occurring in hospital and nonhospitalenvironments have some differences despite both being associated with situations of social vulnerability and health care failures. However, it is necessary to better target the actions directed at the reflection on health surveillance.